2018
DOI: 10.4103/ijd.ijd_624_16
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of zinc and iron levels in the serum and hair of women with androgenetic alopecia: Case–control study

Abstract: Background:Although female androgenetic alopecia (FAGA) occurs in genetically susceptible women, some trace elements may play an important role.Aim of the Study:This study aimed to evaluate serum and hair zinc and iron levels in patients with FAGA and to compare the findings with normal controls.Patients and Methods:A case–control study that was conducted at Dermatology Clinic in Basra General Hospital, Basra, Iraq. The participants were divided into two groups: The first group consisted of 27 women with FAGA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
16
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 27 publications
2
16
1
1
Order By: Relevance
“…Serum zinc was significantly lower in patients with androgenetic alopecia compared to controls 15 . Similar results were found in studies comparing patients with AA to controls and comparing patients with female androgenetic alopecia to controls, with significantly lower zinc in the diseased population 22,23 …”
Section: Mineralssupporting
confidence: 78%
“…Serum zinc was significantly lower in patients with androgenetic alopecia compared to controls 15 . Similar results were found in studies comparing patients with AA to controls and comparing patients with female androgenetic alopecia to controls, with significantly lower zinc in the diseased population 22,23 …”
Section: Mineralssupporting
confidence: 78%
“…Even more, the aromatase enzyme activity at the frontal area in women was 6 times more active than that in men. (25) The investigators found that the mean ferritin level in patients with androgenic alopecia was statistically significantly lower than in normal subjects without hair loss. Dermatologists commonly assess the serum iron status in women with AGA because of the assumption that iron deficiency can cause alopecia.…”
Section: Serum Ferritinmentioning
confidence: 98%
“…A alopecia androgenética é uma doença na qual a queda de cabelo ocorre devido à predisposição genética, que pode ocorrer em qualquer idade após a puberdade e em ambos os sexos. É uma alopecia dependente de andrógeno em indivíduos geneticamente predispostos, em que ocorre conversão dos fios em cabelos miniaturizados (Dhaher & Yacoub, 2018).…”
Section: Introductionunclassified